The island effect: a sociospatial theory of health. - Halliday, Kathryn (International Journal of Population Data Science, 2018)
Background Birthweights are found to be significantly greater on Scottish islands compared to mainland Scotland. This ’island effect’ remains even after adjusting for numerous confounding factors (e.g. ethnicity, socioeconomic factors, smoking, pollutants) that dissolve any significant correlation between locations of varying degrees of rurality and birthweight on the mainland. An unexplored factor is therefore indicated to be conferring a protective advantage for maternal/foetal health on the islands. Objectives My (PhD) project intends to investigate the island effect. Its dominant discourse will concern the social worlds derived from living in communities of such unique physical geography, most notably the islands’ remoteness. I am interested in how the physical and social character of island communities is distinguishable from those on the mainland and may consequently advantage maternal and foetal health via mediating psychosocial mechanisms. Methods I have recruited a mixed-methods approach. A quantitative phase will use R coding software to analyse a number of administrative datasets linked to census data obtained from the Scottish Longitudinal Study. Secondly, a more qualitative fieldwork phase will apply immersive, interview and participant observation techniques on three of the islands (Skye, N.Uist, Shetland) in order to enhance the project’s overall insights and subsequent conclusions. Findings This project is pending. Currently in its first of three years allocated for completion, there are no significant outputs to date. Conclusions It is hypothesised that the islands’ physical circumstances may scaffold particular social values and practices that enhance psychosocial benefits gained from greater informational, instrumental, and emotional support that together comprise greater social capital. If this is the case, the project will illustrate the role and importance of place as socially experienced, with meaningful effects upon psychological and (thereby) physical health outcomes.